Demystifying endoscopic retrograde cholangiopancreatography (ERCP) - Magno Pereira, Vítor (2017)
Background: For many years, ERCP was avoided in pregnancy given the concerns regarding the adverse effects that, with special focus on radiation, could occur in the developing fetus. However, the postponement or rejection of ERCP in pregnant women, may lead to a higher risk for mother and fetus, especially when the indication is unequivocal, namely cholangitis, biliary pancreatitis and symptomatic choledocholithiasis. Summary and key messages: This review aims to summarize the scarce literature on the subject in order to plan ERCP in pregnancy with the highest safety. The use of techniques that reduce radiation and increase the protection of pregnant women allow radiation levels far below the safety limits. We also discuss the various alternatives of ERCP without radiation. EUS can eliminate the need for ERCP with doubtful choledocholithiasis and plan the best approach in those with previous evidence. The possibility of performing “ERCP” with a linear echoendoscope uniquely under ultrasound control has been described. Conversely, the two-step strategy (initial sphincterotomy with stent placement without fluoroscopy and after delivery, ERCP with lithiasis extraction) proved to be safe obviating fluoroscopy. In conclusion, ERCP can be performed in pregnancy safely and effectively with minimal radiation or even no-radiation at all.